Performance Of The Ombudsman Representative Of Bengkulu In Handling Public Service Complaaints - Sulpani, Pidri; Asnawati, Asnawati; Imanda, Antonio (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
This study aims to determine the performance of the Bengkulu Representative Ombudsman in handling public complaints. This study uses qualitative methods, with data collection techniques using observation, interviews and documentation. Researchers using kumorotomo's performance theory the results of this study show the performance of the bengkulu representative ombudsman in handling public service reports. Based on the results of the study, it can be seen that the performance of the Bengkulu Provincial Ombudsman representative in handling public service complaints are: (1) employee efficiency of the bengkulu province representative Ombudsman office totaling 19 employees consisting of 4 assistants. Furthermore, the ombudsman representative of the province is sufficient to carry out the duties and functions of the Ombudsman and the completion time of the Ombudsman complaint is 14 working days, the Ombudsman gets funds from the state revenue and expenditure budget (apbn) the funds are used to handle cases that go to the Ombudsman representative of bengkulu province . (2) the effectiveness of the settlement of public service cases is the task of the Ombudsman because the Ombudsman prioritizes public services that have been regulated by the government in the 2008 law on public services, the purpose of completing public services is to reduce extortion against the government and the relevant agencies regarding public services. Furthermore, the conditions imposed by the Ombudsman representative of the Bengkulu Province in handling complaints are carried out fairly and openly. (3) justice, inside the ombudsman office in completing a report, the Ombudsman office employee is guided by the existing standard operating procedures (sop) and the ombudsman does not take sides with either the reported or the reported parties. (4) responsiveness from the results of reports from the public the Ombudsman performs work on public complaints in accordance with existing procedures, the Ombudsman is a public service that is always open in deciding problems with public services.